Diffusion of Lifelong Learning Policy. The Case of Recognition, Validation and Accreditation of Learning Outcomes - JungEun Lee; Talmadge C. Guy (Adult Education Research Conference, 2013)
The purpose of this study is to understand the diffusion and adoption of lifelong learning policy discourses at the global and national levels by examining the policies of recognition of learning outcomes across 35 countries in Europe, employing content analysis and statistical analysis. Findings, conclusions and limitations are discussed.